2019
DOI: 10.1002/smll.201901704
|View full text |Cite
|
Sign up to set email alerts
|

Controlling DNA Tug‐of‐War in a Dual Nanopore Device

Abstract: Methods for reducing and directly controlling the speed of DNA through a nanopore are needed to enhance sensing performance for direct strand sequencing and detection/mapping of sequence‐specific features. A method is created for reducing and controlling the speed of DNA that uses two independently controllable nanopores operated with an active control logic. The pores are positioned sufficiently close to permit cocapture of a single DNA by both pores. Once cocapture occurs, control logic turns on constant com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 48 publications
(131 reference statements)
2
84
0
Order By: Relevance
“…The control logic was run in real‐time (MHz clock rate) on a field programmable gate array (FPGA). We modified our previously designed tug‐of‐war control process to permit loading reagent in the common fluidic chamber above the two nanopores and to screen out short‐fragments (Section S2 and Figure S1, Supporting Information). Once co‐capture is achieved, the competing voltage forces at V 1 and V 2 lead to a tug‐of‐war and reduce the DNA speed during sensing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control logic was run in real‐time (MHz clock rate) on a field programmable gate array (FPGA). We modified our previously designed tug‐of‐war control process to permit loading reagent in the common fluidic chamber above the two nanopores and to screen out short‐fragments (Section S2 and Figure S1, Supporting Information). Once co‐capture is achieved, the competing voltage forces at V 1 and V 2 lead to a tug‐of‐war and reduce the DNA speed during sensing.…”
Section: Resultsmentioning
confidence: 99%
“…While prior work leveraged control logic for automated recapture and sensing of molecules with single nanopores, our approach is distinctive in a few ways. First, our device employs a dual‐pore architecture . By having the dual pores sufficiently close, our prior work shows the DNA can be captured simultaneously by both pores and exist in a “tug‐of‐war” state where competing electrophoretic voltage forces are applied at the pores .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The doublenanopore system opens up a new path to the mechanical trapping of DNA in solid-state nanopores, and it is a promising technique to measure a wide range of biomolecules with the advantages of being label-free, and having a high signal-to-noise ratio and low cost. It can efficiently confine and trap the DNA molecules to slow down DNA translocation and can also be used to study the physics of this nanoscale tug-of-war on DNA [41].…”
Section: Two Nanopores Systemmentioning
confidence: 99%
“…A range of methods to slow down the polymer in its passage through the nanopore have been reported, an early review can be found in [32] (but also see [33]). More recent work can be found in [34][35][36][37][38][39][40]. The primary aim in all of the above slowdown methods is to allow discrimination of bases in DNA and residues in proteins (and, in one case, unfolding of the protein as well [34]).…”
Section: Polymer Position Controlmentioning
confidence: 99%